Child-Centred Care in HIV Service Provision for Children in Resource Constrained Settings: A Narrative Review of Literature - Chipo Mutambo; Kemist Shumba; Khumbulani W. Hlongwana (AIDS Research and Treatment)
Introduction. Child-centred care approaches are increasingly gaining traction in healthcare; and are being applied in the delivery of HIV care for children in resource constrained settings. However, very little is known about their potential benefits. Methods. We synthesised literature from primary and secondary publications exploring the philosophical underpinnings of the concept of child-centred care, and its application to HIV service delivery for children in resource constrained settings. We concluded the review by suggesting a conceptual framework for mainstreaming and integrating child-centred care approaches in the management of HIV in resource constrained settings. Results. The philosophical underpinnings of child-centred care stem from human rights (child-rights), holism, the ecological model, and life-cycle approaches. Although there is no standard definition of child-centred care in the context of HIV, the literature review highlighted several phrases used to describe the “child-centredness” of HIV care for children. These phrases include: (i) Respect for child-healthcare rights. (ii) Using the lifecycle approach to accommodate children of different ages. (iii) Provision of age-appropriate HIV services. (iv) Meaningful participation and inclusion of the child in the healthcare consultation process. (v) Using age-appropriate language to increase the child’s understanding during healthcare consultations. (vi) Age-appropriate disclosure. (vii) Primary caregiver (PCG) participation and preparation (equipping the PCGs with information on how to support their children). (viii) Creation of a child-friendly healthcare environment. (ix) Consideration of the child ecological systems to have a holistic understanding of the child. (x) Partnership and collaborative approach between children, PCGs, and healthcare workers (HCWs). Conclusion. Child-centred care approaches can potentially increase child-participation, promote positive health outcomes and resilience in children living with a communicable, highly stigmatised and chronic condition such as HIV. More evidence from controlled studies is required to provide concrete results to support the application of child-centred care approaches in HIV care services.